Collaborative Governance dalam Inovasi Daerah: Studi Kasus : Pembangunan Taman Median Jalur Hijau Km.55 – Simpang Kualo Pangkalan Kerinci - Nasruddin, Nasruddin (Badan Riset dan Inovasi Daerah Kabupaten Pelalawan, 2023)
The construction of the km. 55 green lane median park- Simpang Kualo Pangkalan Kerinci, is a program/ activity that is motivated by the lack of Green Open Space (RTH) and the Inability of The Regional Budget (APBD) while development must be always taken placed. So that, the Regional Government of Pelalawan Regency needs to enforce development efforts that are innovative, creative and adaptive. For this reason, collaboration with the company as the main actor in financing is required. The purpose of this study is to identify and analyze how the pattern of collaborative governance implementation in regional innovation in the construction of the km. 55 Green Lane Median Park- Simpang Kualo Pangkalan Kerinci. This research uses qualitative analysis using descriptive research. The result of this research is collaborative action in regional innovation in the construction of the Km. 55 Green Lane Median Park- Simpang Kualo Pangkalan Kerinci which is carried out by 5 actors based on the Penta Helix (PH) concept, namely the Pelalawan Regency Government, third parties (companies), academics, media center and society. Analysis of the collaboration process is carried out in 4 (four) stages, namely: 1) initial conditions, 2) Institutionalization, 3) facilitative leadership, and 4) collaboration processes. At this stage of the collaboration process is carried out by face-to-face dialogue, field observations, construction and transfer of assets. The result of this research will contribute to improve development financing and the quality of the environment and society.